Mind hacking how to change your mind for good in 21 days - Hargrave, John Sir (Gallery Books, 2016)
Through a 21-day, 3-step training program, this book lays out a simple yet comprehensive approach to help you rewire your brain and achieve healthier thought patterns for a better quality of life. It hinges on the repetitive steps of analyzing, imagining, and reprogramming to help break down barriers preventing you from reaching your highest potential